Associations between common sleep disturbances and cardiovascular risk in patients with obstructive sleep apnea: A large-scale cross-sectional study - Zhang, Xiaoman; Huang, Weijun; Xu, Huajun; Li, Xinyi; Wang, Fan; Wu, Kejia; Li, Chenyang; Liu, Yupu; Zou, Jianyin; Zhu, Huaming; Yi, Hongliang; Guan, Jian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives Studies have shown that obstructive sleep apnea (OSA) is inextricably linked with cardiovascular diseases (CVD). However, the roles of certain common sleep disturbances, such as low slow-wave sleep, excessive daytime sleepiness and short sleep duration, in the pathogenesis and progression of CVD in patients with OSA have not been determined. Therefore, we conducted a large cross-sectional study to explore the effect of low slow-wave sleep, excessive daytime sleepiness and short sleep duration on the risk of CVD in patients with OSA. Methods Subjects were consecutively enrolled to participate in the sleep center of Shanghai Jiao Tong University Affiliated Sixth People’s Hospital. All OSA patients were diagnosed by standard polysomnography, while controls were all simple snorers. A total of 4,475 participants were strictly recruited. The Framingham Risk Score were employed to assess the 10-year risk of CVD, and logistic regression was used to measure the association between sleep disturbances and the moderate-to-high CVD risk. Results In the whole cohort, OSA, excessive daytime sleepiness, and low slow-wave sleep were all risk factors for the moderate-to-high 10-year CVD risk (odds ratio [OR] = 3.012, 95% confidence interval [CI] 2.418–3.751; OR = 1.407, 95% CI: 1.228–1.613, and OR = 0.973,95% CI: 0.967–0.980), but sleep duration did not contribute significantly to that risk. Whether in patients with OSA and controls, low SWS (<12.8%) could increase the risk of CVD. Subjective excessive daytime sleepiness would significantly increase the risk of CVD only in patients with severe OSA. Conclusion It is important to pay more attention to the impact of sleep on cardiovascular health. Patients with sleep disturbances should adopt a healthy lifestyle and undergo regular follow-up of cardiovascular indicators to prevent cardiovascular complications. Trial registration [http://www.chictr.org.cn/showproj.aspx?proj=43057], identifier [ChiCTr1900025714].